Nationwide survey of patients' and doctors' perceptions of what is needed in doctor - patient communication in a Southeast Asian context - Trung Quang Tran; A. J. J. A. Scherpbier; Jan van Dalen; Dung Do Van; Elaine Pamela Wright (BMC, 2020)
Abstract Background Asian countries are making efforts to apply the partnership model in doctor-patient communication that has been used effectively in Western countries. However, notable differences between Western and Asian cultures, especially the acceptance of a hierarchical order and little attention to individuality in Asian cultures, could mean that the application of the partnership model in Vietnam requires adaptation. The study aimed to investigate whether communication models used in the Western world are appropriate in Southeast Asia, and to identify key items in doctor-patient communication that should be included in a doctor-patient communication model for training in Vietnam. Methods In six provinces, collaborating medical schools collected data from 480 patients using face-to-face surveys with a structured guideline following a consultation session, and from 473 doctors using a cross-sectional survey on how they usually conduct consultation sessions with patients. Data collection tools covered a list of communication skills based on Western models, adapted to fit with local legislation. Using logistic regression, we examined whether doctor patient communication items and other factors were predictors of patient satisfaction. Results Both patients and doctors considered most elements in the list necessary for good doctor-patient communication. Both also felt that while actual communication was generally good, there was also room for improvement. Furthermore, the doctors had higher expectations than did the patients. Four items in the Western model for doctor-patient communication, all promoting the partnership relation between them, appeared to have lower priority for both patients and doctors in Vietnam. Conclusion The communication model used in the Western world could be applied in Vietnam with minor adaptations. Increasing patients' understanding of their partner role needs to be considered. The implications for medical training in universities are to focus first on the key skills perceived as needing to be strengthened by both doctors and patients. In the longer term, all of these items should be included in the training to prepare for the future.